Myter om velferd og velferdsstaten - Christensen, Karen; Syltevik, Liv Johanne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Post-war expansion of the welfare state is one of the most central changes in Norwegian society today and is often a topic in public debate. When certain conceptions about the welfare state are developed and they are no longer based on systematic analyses but rather ideas and attitudes, they can turn into myths. However, to be termed myths requires documentation, and here social research plays an important role. This book rejects and elaborates central myths in the public debate about the welfare state. The book is structured as an anthology, written by six welfare sociologists at the University of Bergen. The first article introduces the history of The Myth of the Welfare State, a book published by Pax in 1970, then revised a few years later, and with a follow-up version in 1995, 25 years after that. The book became a flaming light within the social policy debate, because it criticized the welfare state for not solving the problem of poverty. Although this problem, relatively seen, is reduced, the following five articles show that, within the framework of the welfare state, there is room for new important critical discussions. One myth focuses on the idea that a combination of a comprehensive state and an active civil society with much voluntary work is not possible. Another concerns the idea that welfare results in dependency. A third is about the "Elder Boom". A fourth concerns single mothers and assumes that these unlawfully try to get access to welfare. And finally, the last discusses the ideas that crime should result in punishment and "prison pain". Together, the articles are a contribution to make the debate about the welfare state richer and more dynamic."